Mozambique 2021 Systematic Country Diagnostic : Coming Together for a Better Future - World Bank (World Bank, Washington, DC, 2021)
In the last five years, since the last Systematic Country Diagnostic (SCD) was written in 2016, Mozambique experienced several severe shocks affecting economic growth, poverty reduction, and stability. These events have changed the context for policy making in Mozambique, calling for a greater focus on governance and accountability, productivity, social safety nets, and a stronger social contract. Despite these new challenges, most of the development trials that were already relevant when the last SCD was written in 2016, remain relevant today.